Islam, extremism and moderation - Akhmetova, Elmira (New Straits Times Press (NSTP), 2015)
Extremism and violence are universal phenomena that have existed throughout human history, and are as such not particular to any specific religious, social or ethnic groups. It threatens all regions, societies, and religions. Yet radicalism is expanding both in the West and East; people are becoming more radical and much brutal in the contemporary period. Extremist’s acts are today committed as much by transnational and supranational groups as by official state parties and organisations, both in the West and in the Muslim world.